Optimasi Formula Lip Balm Avocado Oil dengan Variasi Konsentrasi Cera Alba dan Lanolin menggunakan Metode Simplex Lattice Design (SLD) - Sabiti, Farroh Bintang; Prabu R, Ginanjar; Lisan, Muhammad Fasihul (Sultan Agung Islamic University of Semarang, 2025)
Background: Avocado oil contains vitamins A, E, and D, which play a role in moisturizing, regenerating, and improving the condition of dry skin, making it more elastic and hydrated. In this study, avocado oil was formulated into a lip balm preparation with a combination of cera alba and lanolin as the base. Variations in the concentrations of cera alba and lanolin affect the physical properties of the lip balm; therefore, optimization of their concentrations is required. This study aimed to determine the optimum formula of avocado oil lip balm and the optimal concentrations of cera alba and lanolin used. Methods: A total of eight formulas were established using the Simplex Lattice Design method with the Design Expert 13 software and were prepared through the fusion method. Verification of the optimum formula was statistically analyzed using the One-Sample t-test with SPSS software. Results: The optimum formula was obtained at a proportion of 13.881% cera alba and 3.119% lanolin. The lip balm preparation of the optimum formula exhibited physical characteristics including yellow color, a distinctive oleum cacao odor, semi-solid consistency with good homogeneity, a pH value of 4.6267 ± 0.02517, adhesion time of 2.6267 ± 0.02082 seconds, and spreadability of 3.25 ± 0.25 cm. Conclusion: The avocado oil–based lip balm formulation tested has met the criteria of a good lip balm preparation.